Effect of the presence of brood and fungus on the nest architecture and digging activity of Acromyrmex subterraneus Forel (Hymenoptera, Formicidae) - Santos, Carlos Magno dos; Camargo, Roberto da Silva [UNESP]; Brugger, Mariana [UNESP]; Forti, Luiz Carlos [UNESP]; Santos Lopes, Juliane Floriano (Soc Brasileira Entomologia, 2017)
This study investigated the stimuli that trigger digging behavior inAcromyrmex subterraneus during nest building. The hypothesis was that the presence of the fungus garden and/or brood triggers the excavation of tunnels and chambers. For the experiment, the excavation rate of individually marked workers kept in plastic cylinders filled with soil was recorded. Four treatments were applied: (1) 30 medium-sized workers, 5 g fungus garden and 30 brood items (larvae and pupae); (2) 30 medium-sized workers and 5g fungus garden; (3) 30 medium-sized workers and 30 brood items; (4) 30 medium-sized workers without fungus and brood. After 24 h, morphological parameters of nest structure (length and width of the chambers and tunnels in cm) and the volume of excavated soil were recorded. In contrast to the expected findings, no change in morphological structure, rate of excavation by workers, or volume of excavated soil was observed between treatments, except for tunnel width, which was greater, when no brood or fungus garden was present. Thus, the results do not support the hypothesis that the fungus garden and/or brood are local stimuli for nest excavation or that they mold the internal architecture of the nest. Although this hypothesis was confirmed for Acromyrmex lundii and Atta sexdens rubropilosa, the same does not apply to A. subterraneus. The digging behavior of workers is probably the result of adaptation during nest building in different habitats. (C) 2016 Sociedade Brasileira de Entomologia. Published by Elsevier Editora Ltda.
Keywords: Acromyrmex subterraneus; Digging behavior; Leaf-cutting ants; Nest building; Social insect